Some basic properties of idempotent matrices - Alaa A. Hammodat; Ali A. Bilal; Akram S. Mohammed (College of Education for Pure Sciences, 2008)
Abstract In this paper we give some properties of the zero commut idempotent matrices ,and give some properties of non-singular matrices .